Semantic Features of ‘Noodle’ and its Related Words - Cahyo Ramadhani (Lexicon, 2014)
The word „noodle‟ has different definitions in English dictionaries. The variety of definitions influences the variety of meaning, thus the variety of semantic features of the word. Furthermore, it influences whether a related word could be considered as „noodle‟. To identify the common semantic features of the word „noodle‟, the data are the word „noodle‟ and its definitions in The American Heritage Dictionary of the English Language (AHDEL), Cambridge Academic Content Dictionary (CACD), Funk & Wagnalls Standard Dictionary of English Language (FWSDEL), Merriam-Webster Dictionary (MWD), and Oxford Advanced Learner‟s Dictionary (OALD). To identify if the common semantic features of „noodle‟ are present in noodle-related words, 39 words having the sense “noodle” were collected from Dictionary of Food. The data were analyzed using componential analysis based on theLyons' statement that words and phrases are built upon sense-components. Therefore, the data are broken down into blocks of semantic features, and then marked + if the semantic feature is present, marked +/- if the semantic feature is unlikely present, and marked – if the semantic feature is not present. The result is that the word „noodle‟ in the dictionaries has the ᴍ.ғ. ғʟᴏᴜʀ, ᴍ.ᴡ. ᴇɢɢ, and ʀɪʙʙᴏɴ features in common, with the ʀɪʙʙᴏɴ feature present in all dictionaries, thus the most important semantic feature of „noodle‟. Regarding the 39 noodle-related words, 13 words meet the most important semantic feature of „noodle‟, but only 4 words meet all the common semantic features of „noodle‟, yet 11 words do not meet the common semantic features at all. In brief, the common semantic features of „noodle‟ are not the prerequisite for any word to mean “noodle”.